2020
DOI: 10.1111/icad.12401
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of riparian forest corridors: eight years monitoring the diversity of soil ants in an Andean rural landscape

Abstract: 1. Ecological restoration of riparian forest corridors at the landscape scale can facilitate recruitment of certain flora and fauna, thus possibly helping to maintain viable wildlife populations.2. We evaluated ecological restoration of three corridors between two protected Andean forests. Soil ants and eight environmental variables focused on edaphic conditions were monitored for 8 years following restoration activity. Soil ants were collected in pitfall traps and by leaf litter extraction on 21 plots classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In general, decomposers are less abundant in anthropogenic sites that have been cleared for pasture or other agricultural use [58,59]. However, some authors have found no differences among certain communities, such as ants, among primary forests and forests disturbed for agricultural uses [60].…”
Section: Effects Of Forest Restorationmentioning
confidence: 99%
“…In general, decomposers are less abundant in anthropogenic sites that have been cleared for pasture or other agricultural use [58,59]. However, some authors have found no differences among certain communities, such as ants, among primary forests and forests disturbed for agricultural uses [60].…”
Section: Effects Of Forest Restorationmentioning
confidence: 99%
“…High plant diversity is observed in riparian zones (Handcock et al 1996;Olson et al 2007). Apart from plant diversity, faunal diversity is also high among riparian ecosystems (Ribeiro et al 2012;Vasconcellos et al 2013;Jiménez-Carmona et al 2020;Chen et al 2021).…”
Section: Riparian Ecosystemsmentioning
confidence: 99%
“…Short-term biological benefits include the improvement in fish diversity, soil micro, macrofauna, plant biodiversity, etc. (Opperman and Merenlender 2004;Jiménez-Carmona et al, 2020). The positive impact of restoration on the soil/geomorphology are improved riparian bank, soil structure, soil nutrients, etc.…”
Section: Benefits Of Riparian Restorationmentioning
confidence: 99%